A modified sodium iron phosphate pyrophosphate composite material and its preparation method and application
In the preparation process of polyanionic-sodium ferrophosphate composite positive electrode material, hydrothermal method and sand grinding are used to achieve atomic fusion and element doping of the material, solving the problems of insufficient electrochemical performance and high water absorption, and improving the overall performance of the material.
Patent Information
- Application Number
- CN202411985310.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
At this stage, the preparation of polyanionic-sodium ferrophosphate composite cathode material has problems such as limited raw material particle size, difficulty in achieving atomic fusion, insufficient electrochemical performance and high water absorption.
The nanosheet self-assembled sheet-like composite precursor was prepared by adding soluble doped metal salts and surfactants to the ferrous phosphate solution and reacting under specific temperature and time conditions. Subsequently, the modification of the material and uniform doping of the elements are achieved by sanding, spray drying and heat treatment steps.
The crystal phase structure was successfully optimized, the unimpeded phase was reduced, the energy density, conductivity and other physical and chemical properties of the material were improved, and the water absorption was reduced, which improved the electrochemical performance and the safety of the battery cell.
Smart Images

Figure CN119774575A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a modified sodium iron phosphate pyrophosphate composite material and a preparation method and application thereof. Background Art
[0002] Compared with pumped storage, electrochemical energy storage has the advantages of being less affected by geographical location, having a short construction period and continuously decreasing costs. Currently, lithium-ion batteries occupy a dominant position of more than 90% in electrochemical energy storage. The leading advantage of lithium-ion batteries in the field of electrochemical energy storage has given the green light to the industrial development of sodium-ion batteries with similar models. Sodium-ion batteries with higher cost performance are expected to replace lithium-ion batteries in the field of electrochemical energy storage. The low-temperature safety and other characteristics of sodium-ion batteries have further broadened the application scenarios of supporting energy storage. With the rapid expansion of the energy storage market, it is expected to drive the industrialization process of sodium-ion batteries.
[0003] Currently, the main positive electrode materials for sodium-ion batteries are layered oxides, polyanions, and Prussian blue. Polyanion materials are considered to be the most likely technology route for application in large-scale energy storage due to their naturally excellent structural stability and very low and abundant raw material costs. At present, the preparation of polyanion-sodium iron phosphate pyrophosphate composite positive electrode materials has the following shortcomings: First, the mainstream process uses iron phosphate as one of the main raw materials of NFPP, and uses sand milling spray to prepare the spray precursor. However, since it still cannot escape the limitation of the particle size of the raw materials, it is difficult to achieve atomic-level fusion between the raw materials. Therefore, how to fully fuse iron phosphate with other raw materials to achieve the purpose of optimizing the crystal phase and reducing the impurity phase has become a difficulty in the synthesis of NFPP materials; second, due to the limitation of the preparation process, it is difficult for NFPP materials to achieve the excellent electrochemical properties of the material, so how to dope other elements into NFPP materials to improve the energy density, conductivity and other physical and chemical properties of NFPP materials has become an industry difficulty; third, the strong water absorption of polyanion materials will greatly increase the difficulty and cost of their preservation. At present, the market mainly adopts the establishment of high-specification drying rooms to reduce the moisture in the air to an extremely low level, thereby reducing the material's capture of water molecules in the air, and then reducing the moisture in the material, but this method is extremely expensive and consumes more energy. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a modified sodium iron phosphate pyrophosphate composite material and a preparation method and application thereof, which successfully realizes element doping and material modification during precursor synthesis, thereby optimizing the crystal phase, reducing the impurity phase, improving the energy density, conductivity and other physical and chemical properties of the NFPP material and reducing its water absorption.
[0005] The first object of the present invention is to provide a method for preparing a modified sodium iron phosphate pyrophosphate composite material, comprising the following steps:
[0006] S1. Add a soluble doping metal salt solution and a surfactant to a ferrous phosphate solution, and dropwise add a hydrogen peroxide solution and a hydrofluoric acid solution at 60°C-80°C within 40min-80min, react at 85°C-98°C for 2h-5h after the dropwise addition, and obtain a flaky composite precursor by washing and calcining;
[0007] S2. Dissolve the sheet-like composite precursor, sodium source, phosphorus source and carbon source described in S1 in water, and obtain the modified sodium iron phosphate pyrophosphate composite material by sand milling, spray drying and heat treatment.
[0008] In one embodiment of the present invention, in S1, the soluble doping metal salt is selected from one or more of zirconium salts, lead salts, barium salts and strontium salts;
[0009] The surfactant is selected from one or more of sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate (SDBS) and sodium dodecyl carboxylate.
[0010] In one embodiment of the present invention, in S1, the concentration of the ferrous phosphate solution is 0.5 mol / L-2 mol / L;
[0011] The concentration of the soluble doping metal salt solution is 0.025 mol / L-0.5 mol / L;
[0012] The volume ratio of the ferrous phosphate solution to the soluble doping metal salt solution is 2:(0.7-1.5);
[0013] The added amount of the surfactant is 15mmol / L-25mmol / L.
[0014] In one embodiment of the present invention, in S1, the mass fraction of the hydrogen peroxide solution is 5%-10%;
[0015] The mass fraction of the hydrofluoric acid solution is 30%-50%;
[0016] The volume ratio of the ferrous phosphate solution, the hydrogen peroxide solution and the hydrofluoric acid solution is 1000:(250-500):(3-20).
[0017] In one embodiment of the present invention, in S1, the washing is washing with water until the conductivity of the washing liquid is less than 150 μs / cm;
[0018] The calcination temperature is 500-700°C and the calcination time is 3h-6h.
[0019] In one embodiment of the present invention, in S2, the sodium source is selected from one or more of sodium acetate, sodium hydroxide, sodium carbonate, sodium oxalate, sodium nitrite, disodium hydrogen phosphate, sodium bicarbonate, sodium citrate, anhydrous sodium sulfate, sodium stearate, sodium oleate, sodium tartrate, sodium alginate, sodium carboxymethyl cellulose, sodium lactate, sodium humate, sodium gluconate and sodium ascorbate;
[0020] The phosphorus source is selected from one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphorus pentoxide, sodium ammonium hydrogen phosphate, pyrophosphoric acid, sodium pyrophosphate and hypophosphorous acid;
[0021] The carbon source is selected from one or more of glucose, citric acid, PEG, ascorbic acid, isoascorbic acid, sodium isoascorbate, tea polyphenols and hydroquinone;
[0022] The amounts of the sheet-like composite precursor, the sodium source, and the phosphorus source satisfy the general formula: 4.4 θ n Fe (4-n) F (β*n) (PO4)2P2O7; where θ is the doping metal element and β is the valence state of θ in the chemical formula;
[0023] The molar ratio of the phosphorus source to the carbon source is 1:(0.5-3).
[0024] In one embodiment of the present invention, in S2, the speed of the sand mill is 2000r / min-3000r / min, and the time is 5h-10h;
[0025] The inlet temperature of the spray drying is 230°C-300°C, and the outlet temperature is 90°C-120°C;
[0026] The heat treatment temperature is 400° C.-600° C., and the time is 8 h-20 h.
[0027] The second object of the present invention is to provide a modified sodium iron phosphate pyrophosphate composite material prepared by the method described.
[0028] The third object of the present invention is to provide a sodium ion battery positive electrode, wherein the sodium ion battery positive electrode comprises the modified sodium iron phosphate pyrophosphate composite material.
[0029] A fourth object of the present invention is to provide a sodium ion battery, comprising the sodium ion battery positive electrode.
[0030] The technical solution of the present invention has the following advantages over the prior art:
[0031] (1) The preparation method of the present invention adopts a hydrothermal method, using a small molecule surfactant, hydrogen peroxide and hydrofluoric acid to prepare a sheet-like composite precursor of a self-assembled nanosheet with preferential growth of the {002} crystal face. The exposure of this crystal face is conducive to the cationic substitution of Fe 3+ It enters the iron phosphate lattice and significantly increases the {002} plane spacing. The increase in the plane spacing is beneficial to the deintercalation of sodium ions and improves the electrical properties of the sodium iron pyrophosphate material.
[0032] (2) The prepared self-assembled sheet-like composite precursor has the advantages of large specific surface area, easy breakability, and better fusion with other raw materials. In addition, since the doped elements have been fully fused with iron phosphate at the atomic level during the preparation of the composite precursor, they can be uniformly and efficiently doped into the material during the subsequent heat treatment process, thereby successfully modifying the material.
[0033] (3) The modified sodium iron phosphate pyrophosphate composite material described in the present invention improves the ionic conductivity of the material by doping metals such as zirconium, lead, barium and strontium, and improves the electronic conductivity of the material by doping with fluorine. The combination of doped cations and anions can effectively improve the problem of poor conductivity of the sodium iron phosphate pyrophosphate material, thereby effectively improving its electrochemical performance.
[0034] (4) The F-Na bond formed by the fluoride ions and sodium ions in the modified sodium iron phosphate pyrophosphate composite material of the present invention has a hydrophobic effect, which can effectively reduce the water absorption of the material, reduce the flatulence caused by the water absorption of the material during the subsequent charging and discharging process, and effectively improve the safety of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0036] Figure 1 This is a scanning electron microscope image of the composite precursor in Test Example 1 of the present invention;
[0037] Figure 2 The charge and discharge curve of the button cell made of the modified sodium iron phosphate pyrophosphate composite material of Example 1 in Test Example 2 of the present invention at 0.1C;
[0038] Figure 3 The charge and discharge curves of button cells made of the modified sodium iron phosphate pyrophosphate composite materials of Example 1 and Comparative Example 1 in Test Example 2 of the present invention at 0.1C;
[0039] Figure 4 The charge and discharge curves of button cells made of the modified sodium iron phosphate pyrophosphate composite materials of Example 1 and Comparative Example 2 of the present invention at 0.1C are shown;
[0040] Figure 5 The charge and discharge curves of button cells made of the modified sodium iron phosphate pyrophosphate composite materials of Example 1 and Comparative Example 3 in Test Example 2 of the present invention at 0.1C. DETAILED DESCRIPTION
[0041] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0042] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.
[0043] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.
[0044] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0045] Example 1
[0046] The modified sodium iron phosphate pyrophosphate composite material and the preparation method thereof of this embodiment specifically include the following steps:
[0047] S1. Take 58.8g of iron powder (purity of 95%) and put it into a reactor. Then add 1L of 3.0mol / L dilute phosphoric acid to react with stirring. If the iron powder at the bottom of the reactor no longer reacts, filter it to obtain a ferrous phosphate solution.
[0048] S2, dissolving 22.82 g of zirconium nitrate pentahydrate (purity: 99%) in 537 mL of deionized water to obtain a zirconium nitrate solution;
[0049] S3, add the above zirconium nitrate solution and 5.79g sodium dodecyl sulfate to the above ferrous phosphate solution, heat it to 65°C, and then drop 250mL of 9% hydrogen peroxide solution and 11mL of 40% hydrofluoric acid solution within 60min, heat it to 95°C again after the addition is complete, keep it warm for 3h, and discharge;
[0050] S4, after unloading, washing with pure water until the conductivity of the washing liquid is less than 150 μs / cm, and then calcining at 600° C. for 5 h to obtain a composite precursor;
[0051] S5, weighing 159.6g of the composite precursor, 61.67g of anhydrous sodium carbonate (purity of 99.5%), 7.02g of ammonium dihydrogen phosphate monohydrate (purity of 99%), 23.06g of anhydrous glucose (purity of 99%) and 750mL of deionized water to prepare a raw slurry with a solid content of 30%;
[0052] S6, placing the raw slurry in a sand mill for sand grinding at a speed of 2500 r / min for 6 hours to obtain a sand-ground slurry;
[0053] S7, dry-spraying the sand-milled slurry, with an inlet temperature of 250° C. and an outlet temperature of 100° C., to obtain a spray precursor;
[0054] S8. The spray precursor is heat treated at 500° C. for 12 h in a nitrogen environment to obtain a modified sodium iron phosphate pyrophosphate composite material.
[0055] Example 2
[0056] The modified sodium iron phosphate pyrophosphate composite material and the preparation method thereof of this embodiment specifically include the following steps:
[0057] S1. Take 58.8g of iron powder (purity of 95%) and put it into a reactor. Then add 1L of 3.0mol / L dilute phosphoric acid to react with stirring. If the iron powder at the bottom of the reactor no longer reacts, filter it to obtain a ferrous phosphate solution.
[0058] S2, dissolving 9.11 g of barium hydroxide (purity: 99%) in 537 mL of deionized water to obtain a zirconium nitrate solution;
[0059] S3, add the above zirconium nitrate solution and 5.79g sodium dodecyl sulfate to the above ferrous phosphate solution, heat it to 65°C, and then drop 250mL of 9% hydrogen peroxide solution and 5.3mL of 40% hydrofluoric acid solution within 60min, heat it to 95°C again after the addition is complete, keep it warm for 3h, and discharge;
[0060] S4, after unloading, washing with pure water until the conductivity of the washing liquid is less than 150 μs / cm, and then calcining at 600° C. for 5 h to obtain a composite precursor;
[0061] S5, weighing 160.04g of the composite precursor, 61.67g of anhydrous sodium carbonate (purity of 99.5%), 7.02g of ammonium dihydrogen phosphate monohydrate (purity of 99%), 23.06g of anhydrous glucose (purity of 99%) and 750mL of deionized water to prepare a raw slurry with a solid content of 30%;
[0062] S6, placing the raw slurry in a sand mill for sand grinding at a speed of 2500 r / min for 6 hours to obtain a sand-ground slurry;
[0063] S7, dry-spraying the sand-milled slurry, with an inlet temperature of 250° C. and an outlet temperature of 100° C., to obtain a spray precursor;
[0064] S8. The spray precursor is heat treated at 500° C. for 12 h in a nitrogen environment to obtain a modified sodium iron phosphate pyrophosphate composite material.
[0065] Comparative Example 1
[0066] The method is basically the same as Example 1, except that the composite precursor is not prepared in advance, and specifically includes the following steps:
[0067] S1. Weigh 150.8 g of ferric phosphate, 8.80 g of zirconium fluoride, 61.67 g of anhydrous sodium carbonate (purity: 99.5%), 7.02 g of diammonium phosphate monohydrate (purity: 99%), 23.06 g of anhydrous glucose (purity: 99%), 2.83 g of sodium dodecyl sulfate and 750 mL of deionized water to prepare a slurry with a solid content of 30%;
[0068] S2, placing the raw slurry in a sand mill for sand grinding at a speed of 2500 r / min for 6 hours to obtain a sand-ground slurry;
[0069] S3, dry spraying the sand-milled slurry, with an outlet temperature of 250°C and an outlet temperature of 100°C, to obtain a spray precursor;
[0070] S4. The spray precursor is heat treated at 500° C. for 12 h in a nitrogen environment to obtain a modified sodium iron phosphate pyrophosphate composite material.
[0071] Comparative Example 2
[0072] The method is basically the same as Example 1, except that zirconium and fluorine are not doped, and specifically comprises the following steps:
[0073] S1. Take 58.8g of iron powder (purity of 95%) and put it into a reactor. Then add 1L of 3.0mol / L dilute phosphoric acid to react with stirring. If the iron powder at the bottom of the reactor no longer reacts, filter it to obtain a ferrous phosphate solution.
[0074] S2. Add 5.79 g of sodium dodecyl sulfate to the above ferrous phosphate solution, heat it to 65° C., then drop 250 mL of a 9% hydrogen peroxide solution within 60 min. After the addition is complete, heat it to 95° C. again and keep it warm for 3 h before unloading.
[0075] S4, after unloading, washing with pure water until the conductivity of the washing liquid is less than 150 μs / cm, and then calcining at 600° C. for 5 h to obtain a composite precursor;
[0076] S5, weighing 159.6g of the composite precursor, 61.67g of anhydrous sodium carbonate (purity of 99.5%), 7.02g of ammonium dihydrogen phosphate monohydrate (purity of 99%), 23.06g of anhydrous glucose (purity of 99%) and 750mL of deionized water to prepare a raw slurry with a solid content of 30%;
[0077] S6, placing the raw slurry in a sand mill for sand grinding at a speed of 2500 r / min for 6 hours to obtain a sand-ground slurry;
[0078] S7, dry-spraying the sand-milled slurry, with an inlet temperature of 250° C. and an outlet temperature of 100° C., to obtain a spray precursor;
[0079] S8. The spray precursor is heat treated at 500° C. for 12 h in a nitrogen environment to obtain a modified sodium iron phosphate pyrophosphate composite material.
[0080] Comparative Example 3
[0081] The method is basically the same as Example 1, except that the hydrogen peroxide solution and the hydrofluoric acid solution are not added in a dropwise manner, and specifically comprises the following steps:
[0082] S1. Take 58.8g of iron powder (purity of 95%) and put it into a reactor. Then add 1L of 3.0mol / L dilute phosphoric acid to react with stirring. If the iron powder at the bottom of the reactor no longer reacts, filter it to obtain a ferrous phosphate solution.
[0083] S2, dissolving 22.82 g of zirconium nitrate pentahydrate (purity: 99%) in 537 mL of deionized water to obtain a zirconium nitrate solution;
[0084] S3, add the above zirconium nitrate solution and 5.79g sodium dodecyl sulfate to the above ferrous phosphate solution, heat it to 65°C, add 250mL of 9% hydrogen peroxide solution and 11mL of 40% hydrofluoric acid solution at the same time, then heat it to 95°C again and keep it for 3h, then discharge;
[0085] S4, after unloading, washing with pure water until the conductivity of the washing liquid is less than 150 μs / cm, and then calcining at 600° C. for 5 h to obtain a composite precursor;
[0086] S5, weighing 159.6g of the composite precursor, 61.67g of anhydrous sodium carbonate (purity of 99.5%), 7.02g of ammonium dihydrogen phosphate monohydrate (purity of 99%), 23.06g of anhydrous glucose (purity of 99%) and 750mL of deionized water to prepare a raw slurry with a solid content of 30%;
[0087] S6, placing the raw slurry in a sand mill for sand grinding at a speed of 2500 r / min for 6 hours to obtain a sand-ground slurry;
[0088] S7, dry-spraying the sand-milled slurry, with an inlet temperature of 250° C. and an outlet temperature of 100° C., to obtain a spray precursor;
[0089] S8. The spray precursor is heat treated at 500° C. for 12 h in a nitrogen environment to obtain a modified sodium iron phosphate pyrophosphate composite material.
[0090] Comparative Example 4
[0091] The method is basically the same as Example 1, except that the hydrogen peroxide solution and the hydrofluoric acid solution are not added at the same time, and specifically comprises the following steps:
[0092] S1. Take 58.8g of iron powder (purity of 95%) and put it into a reactor. Then add 1L of 3.0mol / L dilute phosphoric acid to react with stirring. If the iron powder at the bottom of the reactor no longer reacts, filter it to obtain a ferrous phosphate solution.
[0093] S2, dissolving 22.82 g of zirconium nitrate pentahydrate (purity: 99%) in 537 mL of deionized water to obtain a zirconium nitrate solution;
[0094] S3, add the above zirconium nitrate solution and 5.79g sodium dodecyl sulfate to the above ferrous phosphate solution, heat it to 65°C, first add 250mL of 9% hydrogen peroxide solution within 60min, then add 11mL of 40% hydrofluoric acid solution within 60min, heat it to 95°C again after the addition is complete, keep it warm for 3h, and unload;
[0095] S4, after unloading, washing with pure water until the conductivity of the washing liquid is less than 150 μs / cm, and then calcining at 600° C. for 5 h to obtain a composite precursor;
[0096] S5, weighing 159.6g of the composite precursor, 61.67g of anhydrous sodium carbonate (purity of 99.5%), 7.02g of ammonium dihydrogen phosphate monohydrate (purity of 99%), 23.06g of anhydrous glucose (purity of 99%) and 750mL of deionized water to prepare a raw slurry with a solid content of 30%;
[0097] S6, placing the raw slurry in a sand mill for sand grinding at a speed of 2500 r / min for 6 hours to obtain a sand-ground slurry;
[0098] S7, dry-spraying the sand-milled slurry, with an inlet temperature of 250° C. and an outlet temperature of 100° C., to obtain a spray precursor;
[0099] S8. The spray precursor is heat treated at 500° C. for 12 h in a nitrogen environment to obtain a modified sodium iron phosphate pyrophosphate composite material.
[0100] Comparative Example 5
[0101] The method is basically the same as Example 1, except that the doped zirconium element is replaced with calcium element, and specifically includes the following steps:
[0102] S1. Take 58.8g of iron powder (purity of 95%) and put it into a reactor. Then add 1L of 3.0mol / L dilute phosphoric acid to react with stirring. If the iron powder at the bottom of the reactor no longer reacts, filter it to obtain a ferrous phosphate solution.
[0103] S2, dissolving 5.90 g of calcium chloride (purity 99%) in 537 mL of deionized water to obtain a calcium chloride solution;
[0104] S3, add the above calcium chloride solution and 5.79g sodium dodecyl sulfate to the above ferrous phosphate solution, heat it to 65°C, and then drop 250mL of 9% hydrogen peroxide solution and 11mL of 40% hydrofluoric acid solution within 60min, heat it to 95°C again after the addition is complete, keep it warm for 3h, and unload;
[0105] S4, after unloading, washing with pure water until the conductivity of the washing liquid is less than 150 μs / cm, and then calcining at 600° C. for 5 h to obtain a composite precursor;
[0106] S5, weighing 159.6g of the composite precursor, 61.67g of anhydrous sodium carbonate (purity of 99.5%), 7.02g of ammonium dihydrogen phosphate monohydrate (purity of 99%), 23.06g of anhydrous glucose (purity of 99%) and 750mL of deionized water to prepare a raw slurry with a solid content of 30%;
[0107] S6, placing the raw slurry in a sand mill for sand grinding at a speed of 2500 r / min for 6 hours to obtain a sand-ground slurry;
[0108] S7, dry-spraying the sand-milled slurry, with an inlet temperature of 250° C. and an outlet temperature of 100° C., to obtain a spray precursor;
[0109] S8. The spray precursor is heat treated at 500° C. for 12 h in a nitrogen environment to obtain a modified sodium iron phosphate pyrophosphate composite material.
[0110] Comparative Example 6
[0111] The method is basically the same as Example 1, except that the surfactant sodium lauryl sulfate is not added, and specifically comprises the following steps:
[0112] S1. Take 58.8g of iron powder (purity of 95%) and put it into a reactor. Then add 1L of 3.0mol / L dilute phosphoric acid to react with stirring. If the iron powder at the bottom of the reactor no longer reacts, filter it to obtain a ferrous phosphate solution.
[0113] S2, dissolving 22.82 g of zirconium nitrate pentahydrate (purity: 99%) in 537 mL of deionized water to obtain a zirconium nitrate solution;
[0114] S3, add the above zirconium nitrate solution and 5.79g sodium dodecyl sulfate to the above ferrous phosphate solution, heat it to 65°C, and then drop 250mL of 9% hydrogen peroxide solution and 11mL of 40% hydrofluoric acid solution within 60min, heat it to 95°C again after the addition is complete, keep it warm for 3h, and discharge;
[0115] S4, after unloading, washing with pure water until the conductivity of the washing liquid is less than 150 μs / cm, and then calcining at 600° C. for 5 h to obtain a composite precursor;
[0116] S5, weighing 159.6g of the composite precursor, 61.67g of anhydrous sodium carbonate (purity of 99.5%), 7.02g of ammonium dihydrogen phosphate monohydrate (purity of 99%), 23.06g of anhydrous glucose (purity of 99%) and 750mL of deionized water to prepare a raw slurry with a solid content of 30%;
[0117] S6, placing the raw slurry in a sand mill for sand grinding at a speed of 2500 r / min for 6 hours to obtain a sand-ground slurry;
[0118] S7, dry-spraying the sand-milled slurry, with an inlet temperature of 250° C. and an outlet temperature of 100° C., to obtain a spray precursor;
[0119] S8. The spray precursor is heat treated at 500° C. for 12 h in a nitrogen environment to obtain a modified sodium iron phosphate pyrophosphate composite material.
[0120] Test Example 1
[0121] The composite precursor of Example 1 was characterized, and the scanning electron microscope image is as follows: Figure 1 As shown. Figure 1 It can be seen that the composite precursor is a sheet structure with a thickness of more than ten nanometers. The structure is loose, fragile, and has a large specific surface area. It can improve the crushing efficiency of the raw materials during the sand grinding process and increase the contact area between the composite precursor and other raw materials. It greatly reduces the atomic diffusion energy barrier between the raw materials during the low-temperature heat treatment process, thereby increasing the yield of active substances in the material and achieving the purpose of improving the electrochemical properties of the material.
[0122] Test Example 2
[0123] The modified sodium iron phosphate pyrophosphate composite materials prepared in Examples 1-2 and Comparative Examples 1-6 were made into button batteries to test their electrical properties, wherein the weight ratio of the electrode components was modified sodium iron phosphate pyrophosphate composite material: conductive agent (acetylene black): binder (PVDF) = 90:5:5; the negative electrode used a sodium sheet, and the electrolyte was NaClO4 with a concentration of 1 mol / L.
[0124] The button cell was tested at a temperature of 25°C and a voltage of 2.0V-4.0V. The charge and discharge performance at 0.1C was as follows: Figure 2-Figure 5 As shown;
[0125] The test results of the first cycle charge and discharge, first effect, etc. are shown in Table 1:
[0126] Table 1
[0127]
[0128] From Table 1 and Figure 2-Figure 5 It can be seen that the embodiment shows excellent electrochemical performance in terms of first cycle charge, first cycle discharge, first efficiency, and rate performance, and the comprehensive performance is more outstanding, which has obvious advantages over the comparative example. During the discharge process of the material in Example 1 at 0.1C, a long discharge platform appears at around 2.8V. This is because the exposure of the {002} crystal plane is conducive to the substitution of cations for Fe 3+ It enters the iron phosphate lattice and significantly increases the {002} plane spacing. The increase in the plane spacing is beneficial to the deintercalation of sodium ions, thereby extending the discharge platform of the material at around 2.8V, which allows the material to release most of its capacity between 2.5V-3.5V.
[0129] Comparing Example 1 and Comparative Example 1, it can be seen that the preparation of the flaky composite precursor effectively improves its electrochemical performance. Regardless of the first cycle of charge and discharge, or the discharge capacity retention rate at 0.5C and 1C, Example 1 is better than Comparative Example 1. On the one hand, because the hardness of the granular iron phosphate is relatively large, the sand grinding efficiency is relatively low. For the same sand grinding time, its degree of crushing is much lower than that of the flaky composite precursor. The low degree of crushing will lead to a smaller specific surface area of iron phosphate and an increase in the atomic diffusion energy barrier of other raw materials during the heat treatment process, and thus it is difficult to achieve the active material yield of the flaky composite precursor. Secondly, when doping elements, although sand grinding can crush the raw material particles to the nanoscale, the uniformity is far less than that of the atomically fused flaky composite precursor, which makes it difficult to dope other elements into the material and the purpose of material modification cannot be achieved.
[0130] Comparing Example 1 and Comparative Example 2, it can be seen that the preparation of the sheet-like composite precursor effectively improves its electrochemical performance. Whether it is the first cycle of charge and discharge, the first efficiency, or the discharge capacity retention rate at 0.5C and 1C, Example 1 is better than Comparative Example 2. This is because Comparative Example 2 did not dope the material with elements, and the effective doping of zirconium and fluorine elements can improve the ionic conductivity of the material and the electronic conductivity of the material. The combination of cations and anions in the doping elements can effectively improve the poor conductivity of the sodium iron pyrophosphate material itself, thereby effectively improving its electrochemical performance.
[0131] Comparison of Example 1 and Comparative Example 3 shows that the preparation of the sheet-like composite precursor effectively improves its electrochemical performance. Whether it is the first cycle of charge and discharge, the first efficiency, or the discharge capacity retention rate at 0.5C and 1C, Example 1 is better than Comparative Example 3. This is because directly adding all the hydrogen peroxide solution and hydrofluoric acid solution to the filtrate will cause too violent reaction, and the resulting product will not be able to form a sheet structure, which ultimately results in the material failing to achieve the excellent performance shown in the examples.
[0132] Comparing Example 1 and Comparative Example 4, it can be seen that the preparation of the sheet-like composite precursor effectively improves its electrochemical performance. Whether it is the first cycle charge and discharge, the first efficiency, or the discharge capacity retention rate at 0.5C and 1C, Example 1 is better than Comparative Example 4. This is because Comparative Example 4 does not drop hydrogen peroxide solution and hydrofluoric acid solution at the same time, which will cause the generated zirconium fluoride to be unable to be uniformly doped into the iron phosphate, thereby failing to achieve the purpose of element doping to be achieved by the present invention.
[0133] Comparison of Example 1 and Comparative Example 5 shows that the preparation of the sheet-like composite precursor effectively improves its electrochemical performance. Whether it is the first cycle charge and discharge, the first efficiency, or the discharge capacity retention rate at 0.5C and 1C, Example 1 is better than Comparative Example 5. This is because other doping elements cannot achieve the goal of modifying the sodium iron pyrophosphate material.
[0134] Comparing Example 1 and Comparative Example 6, it can be seen that the preparation of the sheet-like composite precursor effectively improves its electrochemical performance. The first cycle of charge and discharge in Example 1 is better than that in Comparative Example 6. This is because nanomaterials have a huge specific surface area and a high surface energy, and their tendency to agglomerate is very large. Adding a small molecule surfactant during the synthesis of the composite precursor can effectively reduce the surface energy of the nanomaterial. The surfactant can be quickly adsorbed on the surface of the newly formed nanocrystal seeds, thereby effectively preventing the agglomeration of the material, and then the nanosheets self-assemble into a sheet-like composite precursor.
[0135] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a modified sodium iron phosphate pyrophosphate composite material, characterized in that: The following steps are involved: S1. Add a soluble doping metal salt solution and a surfactant to a ferrous phosphate solution, and dropwise add a hydrogen peroxide solution and a hydrofluoric acid solution at 60°C-80°C within 40min-80min, react at 85°C-98°C for 2h-5h after the dropwise addition, and obtain a flaky composite precursor by washing and calcining; S2. Dissolve the sheet-like composite precursor, sodium source, phosphorus source and carbon source described in S1 in water, and obtain the modified sodium iron phosphate pyrophosphate composite material by sand milling, spray drying and heat treatment.
2. The method for preparing the modified sodium iron phosphate pyrophosphate composite material according to claim 1, characterized in that: In S1, the soluble doping metal salt is selected from one or more of zirconium salts, lead salts, barium salts and strontium salts; The surfactant is selected from one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and sodium dodecyl carboxylate.
3. The method for preparing the modified sodium iron phosphate pyrophosphate composite material according to claim 1, characterized in that: In S1, the concentration of the ferrous phosphate solution is 0.5 mol / L-2 mol / L; The concentration of the soluble doping metal salt solution is 0.025 mol / L-0.5 mol / L; The volume ratio of the ferrous phosphate solution to the soluble doping metal salt solution is 2:(0.7-1.5); The added amount of the surfactant is 15mmol / L-25mmol / L.
4. The method for preparing the modified sodium iron phosphate pyrophosphate composite material according to claim 1, characterized in that: In S1, the mass fraction of the hydrogen peroxide solution is 5%-10%; The mass fraction of the hydrofluoric acid solution is 30%-50%; The volume ratio of the ferrous phosphate solution, the hydrogen peroxide solution and the hydrofluoric acid solution is 1000:(250-500):(3-20).
5. The method for preparing the modified sodium iron phosphate pyrophosphate composite material according to claim 1, characterized in that: In S1, the washing is performed with water until the conductivity of the washing liquid is less than 150 μs / cm; The calcination temperature is 500-700°C and the calcination time is 3h-6h.
6. The method for preparing the modified sodium iron phosphate pyrophosphate composite material according to claim 1, characterized in that: In S2, the sodium source is selected from one or more of sodium acetate, sodium hydroxide, sodium carbonate, sodium oxalate, sodium nitrite, disodium hydrogen phosphate, sodium bicarbonate, sodium citrate, anhydrous sodium sulfate, sodium stearate, sodium oleate, sodium tartrate, sodium alginate, sodium carboxymethyl cellulose, sodium lactate, sodium humate, sodium gluconate and sodium ascorbate; The phosphorus source is selected from one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphorus pentoxide, sodium ammonium hydrogen phosphate, pyrophosphoric acid, sodium pyrophosphate and hypophosphorous acid; The carbon source is selected from one or more of glucose, citric acid, PEG, ascorbic acid, isoascorbic acid, sodium isoascorbate, tea polyphenols and hydroquinone; The amounts of the sheet-like composite precursor, the sodium source, and the phosphorus source satisfy the general formula: 4.4 θ n Fe (4-n) F (β*n) (PO4)2P2O7; where θ is the doping metal element and β is the valence state of θ in the chemical formula; The molar ratio of the phosphorus source to the carbon source is 1:(0.5-3).
7. The method for preparing the modified sodium iron phosphate pyrophosphate composite material according to claim 1, characterized in that: In S2, the speed of the sand mill is 2000r / min-3000r / min, and the time is 5h-10h; The inlet temperature of the spray drying is 230°C-300°C, and the outlet temperature is 90°C-120°C; The heat treatment temperature is 400° C.-600° C., and the time is 8 h-20 h.
8. A modified sodium iron phosphate pyrophosphate composite material prepared by the method according to any one of claims 1 to 7.
9. A sodium ion battery positive electrode, characterized in that: The sodium ion battery positive electrode comprises the modified sodium iron phosphate pyrophosphate composite material according to claim 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode according to claim 9.
Citation Information
Cited By
Preparation method of composite iron phosphate precursor with different ratios of phosphate radicals to pyrophosphate radicals
CN120964751A
Method for preparing composite iron phosphate precursor with different phosphate to pyrophosphate ratios
CN120964751B